(untitled) (De Legibus - Law Journal, 2022)
Transnational company is not a new concept, but its meaning has been maximized by the phenomenon of globalization. The area of ​​influence of these companies goes beyond commercial relations and affects the development of sovereign states to the point of becoming dependent on a private entity. Due to these characteristics, these corporations become oligopolistic cartels with wealth superior to several countries and ideological domination capable of determining global trends of all kinds. They also use various forms of Tax Evasion, often derived from untraceable planning of a tax system and tax inspection of the countries themselves because of the acquired dependence. The present work tries to explain these problems and shows possible solutions through tax harmonization and the application of social mobilization.